The contribution of the target cost tool to managing production costs in economic institutions: Case study of the GMS- les grands moulins du sud -Biskra - groun, malak; djouamaa, smain (Journal of Research in Finance and Accounting, 2022)
This study aims to show the importance of the target cost tool and it’s role, whether in managing and controlling production costs, achieving product quality, or raising the competitiveness of economic institutions...etc, and we chose the GMS- les grands moulins du sud -Biskra to conduct the applied study on it as one of the most important and largest enterprises producing flour, couscous and pastries at the local and national levels, in light of the high market competition and the specificity of this market in itself due to the policies imposed by the government, including the policy of price ceiling Through our field visit to the institution and the analytical study of the various financial statements extracted from the Department of Accounting and Finance and the Department of Production. the study reached a set of results, the most important of which is that the target cost tool contributes to the diagnosis of the state of the institution and its ability to reduce its costs and reach the target sale price, and clarification the important aspects that the institution should re-study and focus on in order to reduce production costs.